Al-Qur’an Di Era Gadget: Studi Deskriptif Aplikasi Qur’an Kemenag - Althaf Husein (Jurnal Studi Al-Qur’an, 2020)
The development of science and technology can reduce the interest and learning of the Koran. An increasingly modern era gave birth to various gadgets in which there are exciting applications and games. Responding to the problem, the government of the Ministry of Religion of the Republic of Indonesia then made an application for the Ministry of Religion’s Qur’an, that the Qur’an can now be studied not only through printing media but turned to applications that are more practical and easier for the community. On the other hand the study of al-Qur’an in the gadget then leaves many problems dilemma around the sacredness of the Qur’an. with a descriptive analytical-writing method, it examines and explores the application of the Ministry of Religion’s Qur’an from its development background, features, patterns of presentation of the Qur’an to its advantages and disadvantages.